The influence of gender and ethnicity on the choice of language in the transaction domain of language use: the case of undergraduates - Granhemat, Mehdi; Abdullah, Ain Nadzimah; Chan, Swee Heng; Helen, Tan (Australian International Academic Centre, 2015)
Multilingual individuals, consciously or unconsciously, are often confronted with having to select one linguistic code over another from within their linguistic repertoires. The choice of a proper linguistic code enables effective communication and could also lead to the promotion of solidarity among interlocutors. The focus of this study was to examine the influence of gender and ethnicity on the choices of languages of Malaysian youths in the transaction domain of language use. In sociolinguistic studies, Domain as a theoretical concept can be employed to explain how language choices and some individual factors—in case of this study gender and ethnicity—related to language choices of multilinguals. Based on a random proportional stratified sampling strategy, a total of 498 undergraduate local students in a Malaysian public university were selected as respondents of the study. The male and female respondents mostly belonged to the three main ethnic groups, i.e. the Malays, Chinese, and Indians. Also some other ethnic minority groups’ members were included in the study. Data about the demographic profiles of the respondents and the choices of languages in the transaction domain of language use was collected through a self administrated questionnaire survey. SPSS software was used to run analyses such as determining the respondents’ most used languages and Chi-Square Test to find out the relationships between variables. According to the results, the linguistic situation in Malaysia is similar to a diglossic situation. Besides, the factor of ethnicity was found to be influential in the choice and use of linguistic codes among the Malaysian youths. But gender was not found to be a determinant of language choice in the transaction domain of language use.